2012
DOI: 10.1016/j.pain.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-induced analgesia in an operant pain model in rats

Abstract: Analgesia is particularly susceptible to placebo responses. Recent studies in humans have provided important insights into the neurobiology underlying placebo-induced analgesia. However, human studies provide incomplete mechanistic explanations of placebo analgesia because of limited capacity to use cellular, molecular, and genetic manipulations. To address this shortcoming, we describe here the development of a rat model of conditioned analgesia in an operant pain assay. Specifically, rats were conditioned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 65 publications
(110 reference statements)
1
33
0
1
Order By: Relevance
“…Interestingly, all these opioid-mediated placebo responses have also been investigated in rodents, and similar mechanisms have been described (150,247,354). For example, Guo et al (150) used the hot-plate test in an attempt to measure the reaction time of mice to a nociceptive stimulus (hot plate) after different types of pharmacological conditioning.…”
Section: Both Endogenous Opioids and Endocannabinoids May Take Part Imentioning
confidence: 99%
“…Interestingly, all these opioid-mediated placebo responses have also been investigated in rodents, and similar mechanisms have been described (150,247,354). For example, Guo et al (150) used the hot-plate test in an attempt to measure the reaction time of mice to a nociceptive stimulus (hot plate) after different types of pharmacological conditioning.…”
Section: Both Endogenous Opioids and Endocannabinoids May Take Part Imentioning
confidence: 99%
“…In vivo receptor-binding techniques show that a placebo activates m-opioid neurotransmission in the dorsolateral prefrontal cortex, the anterior cingulate cortex, the insula, and the nucleus accumbens (Wager et al, 2007;Zubieta et al, 2005). Although all of these studies have been performed in humans, more recent studies in rodents confirm these pharmacological findings (Guo et al, 2010;Nolan et al, 2012;Zhang et al, 2013). For example, by using different antagonists of different subtypes of opioid receptors (m, d, k), Zhang et al (2013) found that placebo analgesia is mediated specifically by the m opioid receptors only.…”
Section: Introductionmentioning
confidence: 97%
“…Support for an opioidergic pathway derives from a large body of literature reporting evidence of reversal of placebo analgesia with an opioid antagonist. 20 This has been shown in a recent operant rat model based on conditioning of a placebo response 21 and human studies. 22 Based on functional MRI, areas of the central nervous system have been identified which appear to be involved in placebo analgesia in response to rectal distention.…”
Section: Neurobiological Approaches To M Anaging Placebo Effectmentioning
confidence: 81%